SENJATA PERANG DALAM KABA CINDUA MATO - Ulfa Putri Aulia; Khairil Anwar; Wasana Wasana (Universitas Andalas, 2021)
This article describes the armaments in the Cindua Mato kaba story. Through a structural approach and analysis of intrinsic elements, there are several descriptions of armaments in this kaba story. War equipments in the story of Kaba Cindua Mato are not only weapons. The domestic animal, the buffalo Si Binuang, is also used as a tool of war in this kaba story. The use of insects, bees, and wasps is also an instrument of war in the Cindua Mato kaba. In addition, knowledge of nature is a means of successful war strategy. Using large stones on the hill and tanyo-tanyo betel leaves is a form of knowledge about Minangkabau nature. The description of armaments in the Cindua Mato kaba story indirectly shows the Minangkabau people's knowledge of technology that utilizes nature. Using camin api combined with sunlight also shows relatively high technological knowledge.